2017
DOI: 10.1038/s41598-017-06160-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic analysis of Paenibacillus sp. SSG-1 and its closely related strains reveals the effect of glycometabolism on environmental adaptation

Abstract: The extensive environmental adaptability of the genus Paenibacillus is related to the enormous diversity of its gene repertoires. Paenibacillus sp. SSG-1 has previously been reported, and its agar-degradation trait has attracted our attention. Here, the genome sequence of Paenibacillus sp. SSG-1, together with 76 previously sequenced strains, was comparatively studied. The results show that the pan-genome of Paenibacillus is open and indicate that the current taxonomy of this genus is incorrect. The incessant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…In the second place, Paenibacillus species have been described in a variety of environments, some of them interacting with other organisms (Finkelshtein et al, 2015;Grady et al, 2016;Xie et al, 2016), which suggests their potential for affecting ecology. Also, strains of the same species showed numerous variations in genome sequences with a high rate of recombination, which makes them prone to exchange DNA fragments by horizontal genetic exchange (Xie et al, 2016;Xu et al, 2017). Likewise, several species of the genus produce diverse antibiotic substances (Zhao et al, 2018;Pasari et al, 2019), which could make them players in the shaping of their ecosystems.…”
Section: Correlation Of the Presence Of Pairs Of Antibiotic Acquired mentioning
confidence: 99%
See 2 more Smart Citations
“…In the second place, Paenibacillus species have been described in a variety of environments, some of them interacting with other organisms (Finkelshtein et al, 2015;Grady et al, 2016;Xie et al, 2016), which suggests their potential for affecting ecology. Also, strains of the same species showed numerous variations in genome sequences with a high rate of recombination, which makes them prone to exchange DNA fragments by horizontal genetic exchange (Xie et al, 2016;Xu et al, 2017). Likewise, several species of the genus produce diverse antibiotic substances (Zhao et al, 2018;Pasari et al, 2019), which could make them players in the shaping of their ecosystems.…”
Section: Correlation Of the Presence Of Pairs Of Antibiotic Acquired mentioning
confidence: 99%
“…Likewise, several species of the genus produce diverse antibiotic substances (Zhao et al, 2018;Pasari et al, 2019), which could make them players in the shaping of their ecosystems. Furthermore, Paenibacillus genomes have a plethora of genes for adaptation, some of which considered to be acquired by HGT (Xie et al, 2016;Xu et al, 2017). Moreover, some studies have considered that the species of the genus evolve not as individual species, but inter-related in a pan-genomic evolution model (Xu et al, 2017).…”
Section: Correlation Of the Presence Of Pairs Of Antibiotic Acquired mentioning
confidence: 99%
See 1 more Smart Citation
“…Comparative genome analyses of Paenibacillus spp. revealed that this capacity is related to a highly diverse gene repertoire and to the HGT trend [143].…”
Section: Possible Unfavorable Consequences Of the Massive Use Of Bmentioning
confidence: 99%
“…spectrum of pathogens and would be a potential and valuable strain to be further 48 assessed for the development of biofungicides.…”
mentioning
confidence: 99%